On the Wage Growth of Immigrants: Israel, 1990-2000 - Yoram Weiss; Zvi Eckstein (Institute for the Study of Labor (IZA), 2003)
This paper develops a descriptive methodology for the analysis of wage growth of immigrants, based on human capital theory. The sources of the wage growth are: (i) the rise of the return to imported human capital; (ii) the impact of accumulated experience in the host country; and, (iii) the mobility up the occupational ladder in the host country. Using human capital theory, we derive a non-linear model that imposes restrictions across the earning equations of natives and immigrants. The two earning functions are estimated jointly, using repeated cross section data. Using data on immigrants from the former Soviet Union to Israel, we find: Upon arrival, immigrants receive no return for imported skills. In the ten years following arrival, wages of highly skilled immigrants grow at 8% a year. Rising prices of skills, occupational transitions, accumulated experience in Israel and economy-wide rise in wages account for 3.4, 1.1, 1.5 and 1.4 percent each. In the long run, the return for schooling converges to .028, substantially below the .069 for natives. We do not reject the hypothesis that the return for experience converges to that of natives, and immigrants receive higher return for their unmeasured skills. We find that there is some downgrading in occupational distribution of immigrants relative to that of natives. Moreover, the average wages of immigrants approach but do not converge to the wages of comparable natives. The main reason for that is the low return to their imported skills.
Keywords: J24; J6; J31; 330; absorption; convergence; immigrants; occupations; wages; Migranten; Einwanderung; Lohn; Humankapital; Bildungsertrag; Schätzung; Israel